The Role of Maqasid Al-Shariah In Mitigating Depression and Promoting Mental Well-Being in Society - Nursyaza Ainaa Khalim; Norfadhilah Mohd Ali (USIM Press, 2025)
In 2019, the Malaysian Ministry of Health recorded that 2.3% of adults and 9.5% of children aged 10–15 experienced mental health issues, with projections indicating a continued increase. Depression, classified as a mental disorder, has been identified as a contributing factor to suicide and a significant impediment to an individual’s productivity and well-being. Mental health disorders can affect anyone, particularly when individuals struggle to regulate their emotions. Such disorders can impair rational thinking and lead to erratic behavior. Statistics on mental health in Malaysia reveal alarmingly high and concerning prevalence rates, influenced by various factors. In this context, Maqasid al-Shariah plays a crucial role in maintaining mental health within society. Maqasid al-Shariah underscores the importance of preserving mental well-being as part of safeguarding religion, which is the foremost principle in its framework. This study employs a qualitative research methodology grounded in data collection and analysis from academic journals, theses, authoritative electronic sources, and other scholarly materials. The primary objective of this study is to analyze the role of Maqasid al-Shariah in mitigating the rising number of suicide cases and, concurrently, to enhance public awareness of effective measures to prevent depression from escalating into a more severe societal issue